Combination of modified biochar and polyurea microcapsules to co‐encapsulate a fumigant via interface polymerization for controlled release and enhanced bioactivity. Issue 1 (12th September 2021) - Ren, Lirui; Hao, Baoqiang; Fang, Wensheng; Zhang, Daqi; Cheng, Hongyan; Li, Qingjie; Yan, Dongdong; Li, Yuan; Wang, Qiuxia; Zhou, Zhiqiang; Jin, Xi; Cao, Aocheng
Abstract: BACKGROUND: Soil fumigants—the most effective agrochemicals for managing soil‐borne diseases—have been used extensively. However, high volatility, moderate toxicity and insufficient effective duration considerably limit their application. In the present study, interface polymerization was used to combine modified biochar (BC) and polyurea microcapsules (MCs) to co‐encapsulate allyl isothiocyanate (AITC), developing a model fumigant for controlled release (AITC@BC‐MCs). RESULTS: The physical characteristics of BC modified by sand‐milling were significantly improved. In addition, chemical properties and morphological features of AITC@BC‐MCs characterized by integrated methods revealed successful preparation of BC‐MCs. Compared with monolayer MCs, BC‐MCs could significantly delay AITC release owing to the composite obstruction effect. Moreover, modifying BC endowed the cargo molecules with a pH‐responsive release property. Additionally, this composite showed a longer persistent duration by prolonging AITC degradation half‐life, which was 3.2–3.5‐fold greater than that of the AITC technical concentrate under different soil conditions. Finally, the control efficacy of the AITC@BC‐MC against pathogens, including nematodes and fungi, as well as against weeds was significantly enhanced at the same dose, but the composite did not inhibit seed germination and growth after 10 days when fumigated soil was aerated. CONCLUSION: Construction of a composite encapsulation system enhanced pesticide efficacy, reduced dose via controlled release and delayed fumigant degradation in soil, indicating the great potential of this strategy for developing an effective and environmentally friendly fumigant formulation. © 2021 Society of Chemical Industry Abstract : The combination of modified biochar and polyurea microcapsules to co‐encapsulate allyl isothiocyanate can enhance pesticide efficacy and reduce fumigant dose by controlling release and prolonging persistent duration.